Chinese customers’ satisfaction with hotels in Hong Kong: determinants and moderating role of Chinese populations - Hoc-Nang Fong , Lawrence; Chau-Min Poon, Priscilla; Suk- Fong Fung, Daisy (2013)
Witnessing the growing demand of hotel accommodation by Chinese tourists, many hoteliers wager their business growth on the Chinese outbound markets. Satisfying Chinese customers becomes a top priority mission of many hotel managers nowadays. In response to this market trend, an extensive range of studies on determinants of customer satisfaction have emerged in recent years. However, little scholarly attention fell into the prioritization of the determinants. Additionally, while comparative research on customer satisfaction was not scant, most of them compared tourist segments characterized with divergent geographical and cultural profiles. Little comparison was made between tourist segments comprising with people originated from different regions of a nation, in particular in the formation of satisfaction. The current study attempts to fill in these research gaps. Drawing on the findings from a survey with 152 Chinese tourists visiting Hong Kong, this study confirms that perceived performance of the hotel is the most important determinant of customer satisfaction, followed by perceived value and customer expectation. The impact of the determinants on customer satisfaction was stronger among Mainland Chinese than Taiwanese/Macanese, which indicates that Taiwanese/Macanese customers were more demanding and more difficult to be pleased than the Mainland Chinese counterparts. Hoteliers are recommended to customize their service as according to the places of origin of their Chinese customers.